Women’s Language Features In The Podcast Stories Of The Soul - Suhesty, Ayu; Sriyono, Sriyono (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
This study aims at determining the women’s language features produced by Najwa Zebian in the podcast Stories of The Souls and its functions of women’s language. This research utilized a descriptive qualitative method to analyze the data. Data were utterances produced by Najwa Zebian indicating women language’s features. The findings of this research revealed that Najwa did not use all of the women’s language features in the podcast Stories of The Soul. The study identified nine women’s language features occurred, such as lexical hedges or fillers, tag questions, rising intonation , hypercorrect grammar , intensifiers as the most dominant used by Najwa in the podcasts, super polite forms , empty adjectives , avoidance of strong swear words , and emphatic stress . However, the result did not give the occurrence of precise color terms. This study also found several functions of women’s language features. All of the functions are applied to the features in the podcast, including expressing uncertainty, starting a discussion, expressing feelings, and softening an utterance.